Marketing Strategy for Dragon Fruit Farming in Sukamaju Village, Telulimpoe District, Sinjai Regency - A.Nurhaq Annizar; Megawati Megawati; Fadilah Nurdin (Sustainable Agribusiness Review, 2026)
This research is motivated by the significant development of dragon fruit farming in Sukamaju Village, which has high production potential but still faces marketing constraints such as dependence on middlemen, which results in suboptimal farmer income. The purpose of this study was to determine strategies for increasing dragon fruit farming income in Sukamaju Village, Tellulimpoe District, Sinjai Regency. This study uses a quantitative descriptive method with a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis as the primary analytical tool to formulate the strategy. Sampling was conduted using purposive sampling of 40 dragon fruit farmers. The analysis results indicate that dragon farming is in a very strong strategic position and has good prospects for development. This is evidenced by a total score of 3.88 for the Internal Factor Matrix (IFAS) and 3.85 for the External Factor Matrix (EFAS). The Internal-External (IE) Matrix analysis place the farm in cell I, within the “Grow and Build” strategy area. Therefore, the most appropriate strategy to implement is an aggressive and intensive strategy. Based on the SWOT Matrix, the priority strategic alternative is the SO (Strengths-Opportunities) Strategy, which focuses on leveraging key strengths such as agro-climate suitability and early harvest times to saize significant market opportunities through digital marketing and processed product development.